2012
DOI: 10.1002/poc.2986
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic investigations in α‐hydroxycarbonyls reduction by BH4

Abstract: BH4‐, a well‐known and widely used reducing agent for carbonyl compounds, has been reported to have the ability to participate in dihydrogen bonding, an interaction with applications in catalysis, stereoselectivity and crystal engineering. Specifically, α‐hydroxycarbonyls are activated for reduction by dihydrogen bonding that occurs between BH4‐ and hydroxyl group. We explored the effect of the interaction on the mechanism of these reactions by examining their activation parameters. We found that dihydrogen bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…It has been shown that reductions with borohydride can be controlled selectively and the rate can be tuned based on manipulating the dihydrogen interactions. 41,42 Basic aqueous solutions of borohydride have also been proposed as a hydrogen storage mechanism 43 and for use in fuel cells. 44 Thus, the water and borohydride system presents a fairly simple system to study hydrogen bonding, but it also has direct relevance to a variety of systems and processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that reductions with borohydride can be controlled selectively and the rate can be tuned based on manipulating the dihydrogen interactions. 41,42 Basic aqueous solutions of borohydride have also been proposed as a hydrogen storage mechanism 43 and for use in fuel cells. 44 Thus, the water and borohydride system presents a fairly simple system to study hydrogen bonding, but it also has direct relevance to a variety of systems and processes.…”
Section: Introductionmentioning
confidence: 99%
“…Given the ubiquity of water as a solvent and the widespread use of borohydride as a reducing agent, the borohydride/water system is important in its own right, but it is also useful in understanding dihydrogen bond dynamics. It has been shown that reductions with borohydride can be controlled selectively and the rate can be tuned based on manipulating the dihydrogen interactions. , Basic aqueous solutions of borohydride have also been proposed as a hydrogen storage mechanism and for use in fuel cells . Thus, the water and borohydride system presents a fairly simple system to study hydrogen bonding, but it also has direct relevance to a variety of systems and processes.…”
Section: Introductionmentioning
confidence: 99%